Conceptual Understanding and Experimental Skills in Physics through Virtual Lab among Learners at Graduate Level - Lekshmi, V; S, Vijayakumar (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Development of scientific concepts and experimental skills are essential components of learning physics and laboratory experiments plays a significant role in this. Laboratory experience helps learners to understand the concepts, laws and theories as well as to develop observation, critical thinking, and reasoning and problem-solving skill. In traditional laboratories, more time is used for familiarisation with the apparatus than for doing experiments and also there is time constraint to explore more. In addition, there is financial constraint as regards purchase of sophisticated equipment. These constraints limit the attainment of conceptual understanding and development of experimental skills of learners; and Virtual lab appears to be a solution for this. Virtual labs provide remote access to simulation-based experiments and it can be accessed anytime, anywhere by learners, which help them to learn according to their pace. Virtual labs also give opportunity for the learners to repeat the experiments by controlling the variables. Present study aims to find out whether the conceptual understanding in Physics and experimental skills among graduate level learners can be enhanced through Virtual lab intervention. For this, the investigators adopted mixed methodology. Pre-test post-test non-equivalent groups design was used for the quasi experimentation. The sample consisted of 80 students at graduate level. Achievement test, rubrics to analyse experimental skills and focus group discussion were used to collect the data. The quantitative data is analysed through independent sample t-test. Findings of the present study revealed that the conceptual understanding in Physics and experimental skills among graduate level learners are enhanced through practicing virtual lab. Virtual labs help to arouse the curiosity among learners and help them to learn basic and advanced concepts in Physics through remote experimentation. Virtual labs provide learning flexibility, conceptual clarity, development of experimental skills and are financially viable in terms of money and time.